2020
DOI: 10.34172/hpp.2020.56
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oleoylethanolamide supplementation on atherogenic indices and hematological parameters in patients with nonalcoholic fatty liver disease: A clinical trial

Abstract: Background: Non-alcoholic fatty liver disease (NAFLD) is the most frequent cause of chronic liver disease in the world. The current interventional trial aimed to evaluate the effects of supplementation with oleoylethanolamide (OEA) in combination with weight loss intervention on some atherogenic indices as well as hematological parameters in patients newly diagnosed with NAFLD. Methods: In this triple-blinded, randomized, placebo-controlled clinical trial, 76 obese patients with NAFLD confirmed by ultra-sonogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
2
10
0
Order By: Relevance
“…Compared with the conventional lipid parameters, the non-HDL-C, TC/HDL-C, AIS, and LCI ratios are better indicators of AS, a disease that is positively associated with FLD [ 46 ]. These ratios have been suggested to be accurate predictors of AS [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the conventional lipid parameters, the non-HDL-C, TC/HDL-C, AIS, and LCI ratios are better indicators of AS, a disease that is positively associated with FLD [ 46 ]. These ratios have been suggested to be accurate predictors of AS [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, as a drug, OEA reduces food intake and body weight gain [20,27,28] in both lean and obese rodents and reduces lipopolysaccharide-induced liver injury in mice [29]. Moreover, it has been demonstrated that OEA reduces lipid synthesis and lipoprotein secretion in hepatocytes [30] and improves HFD-induced liver steatosis in rats [31] and humans [32,33]. Recently, we demonstrated that OEA decreases hepatic lipid accumulation through a peroxisome proliferator-activated receptor γ (PPARγ)-mediated inhibition of hepatic fatty acid uptake and triacylglycerol synthesis [34].…”
Section: Introductionmentioning
confidence: 99%
“…Activation of PPAR is related to the modulation of multiple physiological processes, including cell metabolism, cancer, cardiovascular functioning, and so forth (Jumpertz et al, 2011; Tan et al, 2021; Wagner & Wagner, 2020b). Among the endogenous ligands that activate PPARα are the lipids oleoylethanolamide (OEA) and palmitoylethanolamide (PEA; Carta et al, 2015; Chen et al, 2015; Grygiel‐Górniak, 2014; Tutunchi et al, 2019; Tutunchi, Naeini, Saghafi‐Asl, Farrin, et al, 2020; Tutunchi, Ostadrahimi, Saghafi‐Asl, Hosseinzadeh‐Attar, et al, 2020; Tutunchi, Saghafi‐Asl, & Ostadrahimi, 2020). The biological relevance of PPARα has been focus of study since this receptor has been mapped in the central nervous system (Nisbett & Pinna, 2018; Warden et al, 2016; Wójtowicz et al, 2020), leading to the hypothesis that cerebral functions might be under the influence of PPARα (Nisbett & Pinna, 2018; Warden et al, 2016; Wójtowicz et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Several natural or synthetic agonists of PPARs have been used to study the mechanism of action of these receptors (Nabavi et al, 2020; Puligheddu et al, 2013; Wagner & Wagner, 2020b). In this regard, PPARα is activated by endogenous ligands, including the lipids oleoylethanolamide (OEA) and palmitoylethanolamide (PEA), triggering mechanisms involved in the modulation of multiple biological functions (Carta et al, 2015; Chen et al, 2015; Fidaleo et al, 2014; Fu et al, 2005; Grygiel‐Górniak, 2014; Rodríguez de Fonseca et al, 2001; Tutunchi et al, 2019; Tutunchi, Naeini, Saghafi‐Asl, Farrin, et al, 2020; Tutunchi, Ostadrahimi, Saghafi‐Asl, Hosseinzadeh‐Attar, et al, 2020; Tutunchi, Ostadrahimi, Saghafi‐Asl, Roshanravan, et al, 2020; Tutunchi, Saghafi‐Asl, & Ostadrahimi, 2020). At present, special attention is focused on the localization of PPARα in several tissues suggesting an active role of this receptor on the control of physiological functions.…”
Section: Introductionmentioning
confidence: 99%